Laughter Yoga as a School-based Wellness Program: Supporting the Well-Being of Nishnawbe Youth - Jacky WL Chan (Canadian Society for Studies in Education, 2019)
This paper explores how the participation in Laughter Yoga (LY) could assist in supporting the overall well-being of Nishnawbe youth. Many Nishnawbe youth are at a heightened risk of mental health issues and social inequities that are associated with the (social) stigma and discrimination that is indicative of colonialism. I illustrate these risks and inequities by discussing the effects of colonialism and the Indian Residential Schools. I discuss the educational inequities that impact many First Nations youth and review the province of Ontario's largest coroner's inquest into the tragic deaths of seven Nishnawbe youth in the Canadian city of Thunder Bay as an example of these inequities. I then provide an Indigenous perspective of mental health in Canadian schools and introduce how the use of laughter has been recognized by Indigenous groups around the world as an integral component of community bonding, social interaction, and communal storytelling. Next, I examine the positive physiological and psychological affects that laughter has on the body and how the promotion of laughter is one strategy that could be introduced to advocate an overall sense of wellness. I then explain the concept of LY and the benefits that LY could have in the classroom. This paper concludes with a list of recommendations that will help support educational administrators, educators, and those who work with/for First Nations youth in the implementation of a school-based LY program as an embodied movement wellness practice with/for First Nations youth within Canadian schools.